Bank Size, Risk and Market Discipline with A Deposit Insurance: Evidence of Banking in Indonesia - Sugeng Haryanto; Grahita Chandrarin; Yanuar Bachtiar (AFRE (Accounting and Financial Review), 2019)
The Indonesian banking system has implemented a deposit guarantee. Deposit guarantees are carried out in order to provide a sense of security for customers. Moral hazard tends to be higher in the banking industry This study aims to examine the relationship of bank characteristics with market discipline. Bank characteristics include: capital, bank risk, profitability, efficiency and bank size. The population in this study is banks in Indonesia. The sample selection uses a purposive sampling method. The number of samples of 30 banks with peroide 2009-2015. Data analysis techniques used multiple linear regression. The results showed the profitability and size of the bank affect market discipline. Where profitability and bank size have a positive effect on market discipline. This research has implications for the importance of banks in increasing bank assets, especially for private banks. DOI: https://doi.org/10.26905/afr.v2i2.3717